Pemasaran Influencer Bersponsor: Dampak Orientasi Komersial Konten yang Dibuat oleh Influencer Terhadap Keinginan Pengikut untuk Mencari Informasi - Maulana, Mozart Elka; Riorini, Sri Vandayuli; Rizqulloh, Ariiq; Arighi, Rahmat (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the impact of the commercial orientation of content created by influencers on their followers' willingness to seek information, as well as the impact of the credibility built by influencers through their Instagram. The results show that Instagram's commercial orientation, which combines a focus on customer satisfaction and profitability, has a positive effect on the influencer's credibility. Instagram supports this through various features such as feeds, IG Stories, IGTV, and Reels, which allow influencers to showcase products attractively and build trust with their followers. Furthermore, trust in influencers, who are perceived as more authentic and easier to connect with, enhances their credibility on social media. The credibility of the messages conveyed by influencers through Instagram posts also influences customer decisions, as followers tend to trust content that is more authentic and inspirational. Additionally, followers' willingness to seek more information is influenced by the influencer's credibility, where followers who trust the influencer are more likely to explore further details about the products being promoted. This study shows that good credibility has a significant impact on followers' trust and interest in seeking additional information about the products promoted by influencers.